Transcriptome sequencing analyses uncover mechanisms of citrus rootstock seedlings under waterlogging stress - He, Wen; Luo, Liang; Xie, Rui; Chai, Jiufeng; Wang, Hao; Wang, Yan; Chen, Qing; Wu, Zhiwei; Yang, Shaofeng; Li, Mengyao; Lin, Yuanxiu; Zhang, Yunting; et al. (Frontiers in Plant Science, 2023)
Citrus plants are sensitive to waterlogging, which can cause yield reduction. Their production heavily depends on the rootstock being used for grafting of scion cultivars, and the rootstock is the first organ to be affected by waterlogging stress. However, the underlying molecular mechanisms of waterlogging stress tolerance remain elusive. Here, we investigated the stress response of two waterlogging-tolerant citrus varieties (Citrus junos Sieb ex Tanaka cv. Pujiang Xiangcheng and Ziyang Xiangcheng), and one waterlogging-sensitive variety (red tangerine) at the morphological, physiological, and genetic levels in leaf and root tissues of partially submerged plants. Our data showed that waterlogging stress significantly decreased the SPAD value and root length but did not obviously affect the stem length and new root numbers. The malondialdehyde (MDA) content and the enzyme activities of superoxide dismutase (SOD), guaiacol peroxidase (POD), and catalase (CAT) were enhanced in the roots. The RNA-seq analysis revealed that the differentially expressed genes (DEGs) were mainly linked to ‘cutin, suberine, and wax biosynthesis’, ‘diterpenoid biosynthesis’, and ‘glycerophospholipid metabolism’ in the leaves, whereas were linked to ‘flavonoid biosynthesis’, ‘biosynthesis of secondary metabolites and metabolic pathways’ in the roots. Finally, we developed a working model based on our results to elucidate the molecular basis of waterlogging-responsive in citrus. Therefore, our data obtained in this study provided valuable genetic resources that will facilitate the breeding of citrus varieties with improved waterlogging tolerance.